IMPLEMENTASI METODE WEIGHTED PRODUCT (WP) DALAM MEMBANGUN SISTEM PENDUKUNG KEPUTUSAN PENENTUAN SISWA TELADAN - Suci Ramadhani Arifin; Risky Hermawan Pratama (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2020)
One of the implementations of a decision support system example in the field of education is the determination of exemplary students at the junior high school level. But now the process of determining exemplary students is still done manually with several constraints and tends to take a relatively long time. In response to this, this study builds a website-based decision support system to determine exemplary students using the Weighted Product (WP) method. The results of the study are expected to provide accurate results in the process of selecting exemplary students especially in junior high schools.